Oral hygiene practices, treatment needs and barriers to dental care among adolescents attending special education schools in Shah Alam, Selangor, Malaysia - Wira, Nur Hafizah Nor (2025)
Adolescents with special healthcare needs have been reported to have poor oral health in compared to normal adolescents due to various factors, include sociodemographic backgrounds, oral hygiene practices and perceived barriers. This study aimed to evaluate the oral hygiene practices, oral health status, dental treatment needs, and barriers to dental care of adolescents with special healthcare needs attending special education schools in Shah Alam, Selangor, Malaysia, while also evaluating the association between these barriers and their dental treatment needs. Shah Alam, an urban area in Selangor, Malaysia, was chosen for this study due to the high enrollment of special needs adolescents in special schools in Selangor compared to other states in Malaysia. Conducting the study in Selangor ensures that the findings will be representative of adolescents with special healthcare needs attending special schools across Malaysia. A total of 131 adolescents with different types of special healthcare needs aged 13-18 years old, who fulfilled the criteria, participated in this study. All information on sociodemographic, oral hygiene practices and possible barriers to the dental care of the participant was supplied by the parents as a proxy through an online survey form. The oral examination on Decayed Missing Filled Teeth (DMFT), Simplified Oral Hygiene Index (OHIS) and treatment needs was carried out in the school with teachers in attendance. Statistical analysis was performed using Chi-square test. A p-value less than 0.05 was considered statistically significant. Data was analyzed via the Statistical Package for Social Sciences version 29.0. Over 60% of participants demonstrated good oral hygiene with a mean DMFT and OHIs scores of 0.79 ± 1.49 and 0.73 ± 0.4, respectively. Most participants, (59.5%), brushed their teeth more than once a day, and about 93.9% used fluoridated toothpaste. The barriers perceived by the parents or caregivers where time constrains to bring their child to dental clinic and child dental anxiety. Most of them required oral prophylaxis and restorative treatment. The present study shows no association between barriers to dental care and dental treatment needs. Adolescents with special healthcare needs in the present study generally have a satisfying oral health status. However, improvements in oral hygiene practices are needed and unmet treatment needs remain high. This study also provides a valid picture of barriers to dental care among adolescents with special needs. This study was conducted in an urban area in Selangor, Malaysia and considering that these adolescents had a new set of teeth, therefore, no association was observed between barriers to dental care and dental treatment needs. A multi-centre study area with a larger sample size is recommended for the future studies